BABUR'S HUMANITARIAN AND PHILOSOPHICAL VIEWS (Scientific journal of the Fergana State University, 2024)
In this article, the author analyzed and described the sociocultural and scientific environment of Maverannakhra and India in 16-17 weeks. A takje humanisticheskie and philosophskie vzglyady poeta, Concept love and philosophical-religious concept "Babur-name".